Mo2B, an MBene member with high electrical and thermal conductivities, and satisfactory performances in lithium ion batteries. Issue 1 (6th December 2019) - Zha, Xian-Hu; Xu, Pengxiang; Huang, Qing; Du, Shiyu; Zhang, Rui-Qin
Abstract : Mo2 B, a predicted MBene, shows high thermal and electrical conductivities, and a relatively low migration energy barrier for Li ions. Abstract : Owing to their high specific area, good flexibility and many other unique properties, two-dimensional (2D) materials have attracted extensive attention in the recent two decades. As an analogy to the well-studied MXenes, MBenes also emerged. In this work, Mo2 B, an MBene member, is predicted both in H- and T-type configurations from first-principles calculations. Structural, mechanical, electronic, and thermal properties, and performances in lithium ion batteries (LIBs) for both configurations are investigated. The H-type Mo2 B is found to be the stable structure, which can be transformed into the T-type by applying strains. The elastic constants c 11 in the H- and T-type Mo2 B are respectively calculated to be 187.5 and 157.6 N m −1, which are higher than that in the previously reported Mo2 C. The electronic thermal conductivity and electrical conductivity are investigated based on the semiclassical Boltzmann transport theory. The electrical conductivities for both structures are of the order of 10 6 Ω −1 m −1 . Because of the large phonon contributions, the thermal conductivities in the H- and T-type Mo2 B are much higher than that of the synthesized Mo2 C. Based on a 5 μm flake length, the phonon thermal conductivities at room temperature are calculated to be 146 and 141 W m −1 K −1 respectively for the H- and T-type configurations. The T-type Mo2 B shows promising performances in LIBs. The theoretical volumetric capacity is as high as 2424 mA h cm −3, and the migration energy barrier is as low as 0.0372 eV. These data imply that Mo2 B has widespread applications, such as in conductive films and anode materials.